Impact of evening blue light exposure timing on sleep, motor, and cognitive performance in young athletes with intermediate chronotype - Souissi, Mohamed Abdelkader; Gouasmia, Chadha; Dergaa, Ismail; Faleh, Jihed; Trabelsi, Omar; Weiss, Katja; Rosemann, Thomas; Dhahbi, Wissem; Souissi, Nizar; Knechtle, Beat (Biology of Sport, 2025)
Evening exposure to blue light has been shown to negatively affect sleep patterns and cognitive function. However, the effect of the specific timing of blue light exposure on motor performance and sleep quality in adolescent athletes remains unclear. This study aimed to investigate the impact of evening blue light exposure (BLE) timing on sleep quality, motor performance, and cognitive function in young athletes with intermediate chronotypes. Sixteen male adolescent athletes (age: 15.11 ± 0.92 years, body height: 168.25±7.09 cm, body-mass: 59.49±5.63 kg) participated in a randomized,crossoverstudy with fourconditions: BLE from (i) 7: 30–9: 00 PM, (ii) 9: 00–10: 30 PM, (iii) 10: 30 PM-12: 00 AM, and (iv) control (no BLE). Sleep quality and quantity were evaluated using the Spiegel and Vis-Morgen questionnaires. Selective attention was assessed using the Bells Test, while motor function was tested by dart-throwing accuracy and movement duration. ANOVA indicated substantial main effects of BLE timing on sleep metrics, motor performance, and cognitive function. Total sleep duration was markedly shorter in the 9: 00–10: 30 PM and 10: 30 PM-12: 00 AM conditions relative to the control ( p < 0.001, d = 0.54 [ medium ] and d = 0.87 [ large ], respectively) and the 7: 30–9: 00 PM condition ( p < 0.05, d = 0.28 [ small ] and p < 0.001, d = 0.56 [ medium ], respectively). Dart-throwing accuracy was significantly lower in the 9: 00–10: 30 PM and 10: 30 PM-12: 00 AM conditions versus the control ( p < 0.002, d = 0.77 [ medium ]) and p < 0.001, d = 1.41 [ large ], respectively). Movement duration was significantly longer in these conditions compared to the control ( p < 0.001, d = 1.75 [ large ] and d = 1.51 [ large ], respectively) and 7: 30–9: 00 PM condition ( p < 0.01, d = 1.38 [ large ] and p = 0.002, d = 1.17 [ large ], respectively). Selective attention was significantly lower in the 9: 00–10: 30 PM and 10: 30 PM-12: 00 AM conditions compared to the control ( p = 0.003, d = 0.66 [ medium ] and p < 0.001, d = 0.91 [ large ], respectively). Evening BLE, especially after 9: 00 PM, adversely affects sleep quality, motor performance, and cognitive function in young athletes. These findings underscore the necessity of reducing BLE in the evening to enhance sports performance, optimize training and recovery, and facilitate motor learning for skill development.